From Knowledge Exchange to Business Performance: Evidence of Mentoring as a Mediating Mechanism among MSMEs - Junaidi Junaidi; Suhendri Suhendri; Zulham Zulham (STIE Amkop Makassar, 2026)
This study examines the effect of knowledge sharing on the performance of Micro, Small, and Medium Enterprises (MSMEs) with a mentoring program as a mediating variable among fostered partners of PT Perkebunan Nusantara III. A quantitative approach was employed using a survey method through structured questionnaires. The population consisted of all MSMEs supported by PT Perkebunan Nusantara III, with 96 business actors selected using purposive sampling based on established development criteria. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to evaluate the relationships among variables simultaneously. The results indicate that knowledge sharing has a positive and significant effect on MSME performance. Furthermore, the mentoring program significantly strengthens the influence of knowledge sharing on business performance. This finding suggests that knowledge sharing becomes more effective when supported by mentoring that is relevant, continuous, and aligned with organizational needs. The study provides practical implications for partnership program managers to develop mentoring as a strategic mechanism to improve knowledge transfer and enhance MSME performance.